Newly shed litters contain an abundance of extractable humus carbon in a subalpine forest on the eastern Tibetan Plateau. Issue 9 (17th September 2018) - Yang, Jiaping; Zhang, Yu; Yang, Wanqin; Tan, Bo; Yue, Kai; Fu, Changkun; Ni, Xiangyin; Wu, Fuzhong
Abstract: Humus is an important component of soil organic matter, but little attention has been paid to humus in newly shed litters. Moreover, the influence of climatic factors and chemical composition on the variation in humus carbon (HC) among different litter components and foliar litter in plant functional types is unknown. We conducted a field experiment in a subalpine forest on the eastern Tibetan Plateau in southwestern China from April 2016 to November 2016. Sixty litter collectors were fixed at three sampling sites that had been randomly established in the study area. The collected litter was classified as foliar litter (evergreen tree species versus deciduous tree species and tree species versus shrub species), twig litter, flower and fruit litter, and miscellaneous litter. The results clearly showed that extractable HC was abundant in the newly shed litters and exhibited significant seasonal trends. The concentrations of HC, humic acid carbon (HAC), and fulvic acid carbon (FAC) in the foliar litter were greater than those in the other plant components throughout the study period. In addition, the HC concentrations in four plant components peaked in July. In contrast, the HC concentrations in evergreen tree species stably remained at high levels, with a peak in July. The HAC concentrations in the foliar litter, twig litter, and miscellaneous litter exhibited irregular fluctuation trends, and maxima occurred in August. Furthermore, the total HC stock in the plant components in the study area was 1294.40 kg/hm 2, of which the HAC stock constituted 471.38 kg/hm 2 and the FAC stock constituted 820.02 kg/hm 2 . The results presented here suggest that newly shed litters contain an abundance of extractable HC in this subalpine forest, revealing the initial state of organic carbon in the total alkaline solutions before it is transferred from the plant litter to the soil.